"We Are Sensemakers": The (Anti-)politics of Smart City Co-creation. - Zandbergen, Dorien (Public Culture, 2017)
This essay tackles the anti-politics of smart city co-creation using the case of the Air Quality Egg (AQE) computer device project. Topics discussed are mobilization of the AQE project in the service of corporate innovation and political activism agendas, tension in the AQE project caused by oppositional interest positions, potential of AQE to constitute an open source alternative, physical, social and environmental motivations for joining the project, and legacies of prototyping AQE.